The Making of an RNA Phage Bibliography with Personal Information Retrieval by Microcomputer - Van Styvendaele, B. J. H. (Methods of Information in Medicine, 1979)
The article describes a microcomputer-based system designed for personal storage and retrieval of information. Document description, conversion of data elements into machine-readable form, a bibliographic record structure that can be adapted according to individual requirements together with the necessary routines for document entry, error correction, storage, updating, sorting, searching and retrieval of information is presented. These methods were used in the development of a computergenerated bibliography as illustrated by samples of the final print-outs from different data files. The implementation of a microcomputer-based system for documentary information processing and management at a price and level of complexity which many users can afford is likely to solve problems of information volume, loss, inefficient retrieval and ineffective filing.
Keywords: Microcomputer-based Literature Search System; Personal Information Storage and Retrieval System; RNA Phage Bibliography